Exclusive breastfeeding abandonment in adolescent mothers: a cohort study within health primary services (Revista Latino-Americana de Enfermagem, 2022)
Objective: to analyze the factors associated with the abandonment of exclusive breastfeeding in adolescent mothers during the first 6 months of the infant’s life. Method: this is a cohort study of 105 adolescent mothers followed at the child’s 2-, 4- and 6-months of age. The epidemiological approach was adopted, supported by the positivism paradigm. Exposure variables were those directly related to breastfeeding and sociodemographic, family, maternal and child conditions. Data were collected by interview and analyzed by bivariate and multivariate statistics. The Hazard Ratio (HR) was calculated with a 95% confidence interval (95%CI). The tests were performed, admitting an error type I of 5%. The confidentiality of data was ensured. Results: the cumulative incidences of exclusive breastfeeding abandonment were 33.3%, 52.2% and 63.8%, at 2, 4 and 6 months, respectively. The variables that remain in the final multivariate model were maternal perception of milk quality (HR=11.6; 95%CI 3.6-37.5), pacifier use (HR=1.9; 95%CI 1.2-3.3), and time of first breastfeeding session (HR=1.4; 95%CI 0.5-12.9). Conclusion: the highest abandonment rate occurs before the fourth month. A perception of having poor-quality milk by the adolescent mother and pacifier use are factors that favor the abandonment of exclusive breastfeeding. Determining the factors associated with breastfeeding abandonment may allow their timely management, especially in more vulnerable populations.